Lived experiences of older adults while working in the academe amidst the COVID-19 pandemic: The Philippine context - Lovelyn G. Tipon; Jose Mari Louis Alforque; Jezyl C. Cutamora (Belitung Raya Foundation, Indonesia, 2022)
Background: Despite the rising number of COVID-19 cases in the Philippines and the world, our aging population, especially older adults working in the academe, has not ceased with their desire to provide quality education among our student nurses continuously. Aside from the fact that most of these nursing mentors in the field of education have been closer to the age of retirement, they still opt to continue their passion for teaching. Hence, knowing their lived experiences can be a great anchor on how to support them effectively. Objective: This study aimed to explore the older adults’ lived experiences while working in the academe amidst the pandemic. Methods: A qualitative descriptive phenomenological approach was employed. Purposive sampling was used to select twelve informants based on the set inclusion criteria, such as older adults aged at least 60 years old and above residing within Cebu City, Philippines, who were currently employed as nursing mentors in any private or public academic nursing institution. Colaizzi's method of data analysis was used. Results: Four themes emerged: (1) Diversifying Teaching and Learning Strategies, (2) Labyrinthing Through the Challenges, with three subthemes (Coursing through struggles and adversities, Thriving with the teaching and learning during the pandemic, and Coping with the changes), (3) Strengthening Health, Adhering to Protocols, and (4) Moving Forward with the New Normal, with two subthemes (Adapting to be technologically resilient and Having a positive outlook). Conclusion: The older adults learned to teach, adapt, adjust, and move forward in the academe amidst the pandemic. They keep up with the changes and the challenges despite being an older adult having limited experience and knowledge of the use of technology. They continue to strive, live and be more productive amidst the pandemic.